SEROPREVALENCE OF PORCINE CYSTICERCOSIS IN RURAL VILLAGES OF THE DEPARTMENT OF TUMBES, PERU - García A., Bruno (2011)
The porcine cysticercosis seroprevalence was determined in rural villages of Tum-bes, Peru. Samples from 97% (1872/1927) of pigs, older than 7 months of age, from 17 ruralvillages of Tumbes province, Peru, were analyzed by the Electroimmunotransfer test.Also, village of origin, age, and sex were assessed to determine whether there wasassociation with regard to the presentation of the disease by the Chi square test andlogistic regression analysis. Seroprevalence was 45 ± 2.3%. Villages with higherseroprevalences were La Capitana, Carretas, and Rica Playa (70 ± 7.8, 69 ± 12.3, and 64 ± 6.8% respectively). Seroprevalence in pigs older than 12 months of age was 49 ± 3.1%,while in pigs 8 to 12 months of age was 40 ± 3.3% (p<0.05). There was no statisticaldifference due to sex. The results show that porcine cysticercosis is a serious publichealth problem for the villages surveyed.